A sucrose mouth rinse does not improve 1-hr cycle time trial performance when performed in the fasted or fed state - Trommelen, J.; Beelen, M.; Mullers, M.; Gibala, M. J.; van Loon, L. J. C.; Cermak, N. M (International Journal of Sport Nutrition and Exercise Metabolism, 2015)
Carbohydrate mouth rinsing during exercise has been suggested to enhance performance of short (45-60 min) bouts of high-intensity (>75% VO2peak) exercise. Recent studies indicate that this performance enhancing effect may be dependent on the prandial state of the athlete. The purpose of this study was to define the impact of a carbohydrate mouth rinse on ~1-hr time trial performance in both the fasted and fed states. Using a double-blind, crossover design, 14 trained male cyclists (27 ± 6 years; 5.0 ± 0.5 W·kg-1) were selected to perform 4 time trials of ~1 hr (1,032 ± 127 kJ) on a cycle ergometer while rinsing their mouths with a 6.4% sucrose solution (SUC) or a noncaloric sweetened placebo (PLA) for 5 s at the start and at every 12.5% of their set amount of work completed. Two trials were performed in an overnight fasted state and two trials were performed 2 h after consuming a standardized breakfast. Performance time did not differ between any of the trials (fasted-PLA: 68.6 ± 7.2; fasted-SUC: 69.6 ± 7.5; fed-PLA: 67.6 ± 6.6; and fed-SUC: 69.0 ± 6.3 min; Prandial State × Mouth Rinse Solution p = .839; main effect prandial state p = .095; main effect mouth rinse solution p = .277). In line, mean power output and heart rate during exercise did not differ between trials. In conclusion, a sucrose mouth rinse does not improve ~1-hr time trial performance in well-trained cyclists when performed in either the fasted or the fed state.